Projected Changes to Wintertime Air‐Sea Turbulent Heat Fluxes Over the Subpolar North Atlantic Ocean. Issue 4 (20th April 2023) - Barrell, Christopher; Renfrew, Ian A.; King, John C.; Abel, Steven J.; Elvidge, Andrew D.
Abstract: In wintertime over the subpolar North Atlantic Ocean (SPNA), the strongest surface sensible and latent heat fluxes typically occur just downstream of the sea‐ice edge. The recent retreat in Arctic wintertime sea ice is changing the distribution of these turbulent heat fluxes, with consequences for the formation of the dense waters that feed into the Atlantic Meridional Overturning Circulation. Projections of turbulent heat flux over the SPNA are investigated using output from the HadGEM3‐GC3.1 climate model, produced as part of the sixth phase of the Coupled Model Inter‐Comparison Project. Comparison of two model resolutions (MM: 60 km atmosphere—1/4° ocean and HH: 25 km–1/12°) shows that the HH configuration more accurately simulates historic sea ice and turbulent heat flux distributions. The MM configuration tends to produce too much sea ice in the SPNA, affecting the turbulent heat flux distribution; however, it displays improved performance during winters with less sea ice, increasing confidence in future projections when less sea ice is predicted. Future projections are presented for low (SSP1‐2.6) and high (SSP5‐8.5) emissions pathways. The simulations agree in predicting that, with climate change, the SPNA will see reductions in wintertime sea ice and air‐sea turbulent fluxes later in the 21st century, particularly in the Labrador and Irminger Seas and the interior of the Nordic Seas, and a notable reduction in their decadal variability. These effects are more severe under the SSP5‐8.5 pathway. The implications for SPNA ocean circulation are discussed. Plain Language Summary: In winter over the subpolar North Atlantic Ocean a large amount of heat is transferred from the ocean to the air just off the sea ice. This heat loss drives water mass changes in the ocean, which, in turn, helps drive global ocean circulation. The subpolar North Atlantic is rapidly warming due to fossil fuel emissions, resulting in a large reduction of sea ice that may further impact global climate. We look at predictions of future sea ice loss and its effects on air‐sea heat exchange using some of the latest climate simulations that represent the atmosphere and the ocean at high spatial resolution. These simulations do reasonably well at reproducing the historic climate of the region, so we have some confidence that they are suitable for making predictions of future conditions. We investigate future projections for low and high emissions scenarios, finding that ocean heat loss to the atmosphere will reduce, particularly in the Labrador, Irminger and interior of the Nordic Seas, and by a greater amount under the high emissions scenario. How this could affect the ocean is discussed. Key Points: The climate model HadGEM3‐GC3.1 simulates historic sea ice and turbulent heat fluxes reasonably well, with improvements at higher resolution Upward turbulent heat fluxes are predicted to reduce, particularly in the Labrador and Irminger Seas and the interior of the Nordic Seas Changes in local heat flux maxima are largely governed by ice edge retreat, while overall a reduction in ocean heat loss is projected